2014
DOI: 10.1002/hbm.22439
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of changes in resting‐state functional connectivity patterns in cognitive recovery after stroke: A 3T fMRI pilot study

Abstract: Resting-state studies conducted with stroke patients are scarce. First objective was to explore whether patients with good cognitive recovery showed differences in resting-state functional patterns of brain activity when compared to patients with poor cognitive recovery. Second objective was to determine whether such patterns were correlated with cognitive performance. Third objective was to assess the existence of prognostic factors for cognitive recovery. Eighteen right-handed stroke patients and eighteen he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 60 publications
8
41
0
Order By: Relevance
“…By means of seed-based-connectivity analysis, we found that functional connectivity of the contralesional hemisphere was affected, which is in agreement with our previous studies [Dacosta-Aguayo et al,2014a,b] conducted with stroke patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By means of seed-based-connectivity analysis, we found that functional connectivity of the contralesional hemisphere was affected, which is in agreement with our previous studies [Dacosta-Aguayo et al,2014a,b] conducted with stroke patients.…”
Section: Discussionsupporting
confidence: 91%
“…Previous works showed that localized brain lesions can cause connectivity-based changes in regions that are structurally intact and far from the lesion site [Carter et al, 2010; Carter et al, 2012; Crofts et al, 2011; Dacosta-Aguayo et al, 2014a,b; Golestani et al, 2013; Grefkes et al, 2008; He et al, 2007; Nomura et al, 2010; Ovadia-Caro et al, 2013; Park et al, 2011; Tuladhar et al, 2013; Warren et al, 2009]. The relationship between alterations in functional connectivity after stroke and behavioral outcome/performance has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Our discussion will mainly focus on the motor system, for two reasons: first, the majority of animal studies on focal ischemia model sensorimotor deficits, and therefore the translational link is strongest in this domain; and second, the tools available for probing and interfering with brain circuitry in humans (such as transcranial magnetic stimulation) are most readily applied in the motor system. However, stroke and vascular dementia often have debilitating effects on memory and executive function (Black et al, 2009;Dacosta-Aguayo et al, 2014;Lim et al, 2014). It is quite possible that the rules we define for sensorymotor recovery will not be shared in these other cases, emphasizing the need for both animal models and imaging assessment tools for humans that are geared toward non-sensory-motor aspects of stroke.…”
Section: Introduction: Stroke As a Disease Of Brain Connectivitymentioning
confidence: 96%
“…The DMN, a set of brain regions that typically deactivate during performance of cognitive tasks, has been considered to be involved in the integration of primary perception and high cognitive processing (Andrews‐Hanna, ; Broyd et al, ; Raichle et al, ). Previous studies have suggested that resting‐state DMN dysfunction is related to cognitive impairment in stroke patients (Dacosta‐Aguayo et al, ). In this study, not surprisingly, there were no regions that showed significant FC differences within the DMN in the stroke patients, as the enrolled subjects had good general cognitive function.…”
Section: Discussionmentioning
confidence: 98%